Force transmission and constraint analysis of a 3-SPR parallel manipulator. (December 2018) - Russo, Matteo; Ceccarelli, Marco; Takeda, Yukio
This paper presents an analysis of a novel 3-SPR parallel manipulator with 3 degrees-of-freedom that is characterized by a mobile platform consisting of a single point where all the three open-loop kinematic chains converge. The constraint singularity problem of the mechanism is solved in closed form by computing the Jacobian of the manipulator. Then, the expression of the transmission index is obtained for the 3-SPR manipulator by using the pressure angle definition. In order to evaluate the influence of secondary parameters, an equivalent 6-SPS mechanism is analyzed and its transmission index is computed in the parameter space. Finally, the proposed manipulator is compared to a standard 3-SPR parallel mechanism to investigate the influence of the mobile platform radius over transmission index and workspace volume. The results are discussed in order to highlight the advantages and disadvantages of the proposed structure of parallel manipulator.